Modulating the Pore Architecture of Ice-Templated Dextran Microparticles Using Molecular Weight and Concentration - Kämäräinen, Tero; Kadota, Kazunori; Tse, Jun Yee; Uchiyama, Hiromasa; Yamanaka, Shinya; Tozuka, Yuichi (Langmuir, 2022)
Spray freeze drying (SFD) is an ice templating method used to produce highly porous particles with complex pore architectures governed by ice nucleation and growth. SFD particles have been advanced as drug carrier systems, but the quantitative description of the morphology formation in the SFD process is still challenging. Here, the pore space dimensions of SFD particles prepared from aqueous dextran solutions of varying molecular weights (40-200 kDa) and concentrations (5-20%) are analyzed using scanning electron microscopy. Coexisting morphologies composed of cellular and dendritic motifs are obtained, which are attributed to variations in the ice growth mechanism determined by the SFD system and modulation of these mechanisms by given precursor solution properties leading to changes in their pore dimensions. Particles with low-aspect ratio cellular pores showing variation of around 0.5-1 μm in diameter with precursor composition but roughly constant with particle diameter are ascribed to a rapid growth regime with high nucleation site density. Image analysis suggests that the pore volume decreases with dextran solid content. Dendritic pores (≈2-20 μm in diameter) with often a central cellular region are identified with surface nucleation and growth followed by a slower growth regime, leading to the overall dendrite surface area scaling approximately linearly with the particle diameter. The dendrite lamellar spacing depends on the concentration according to an inverse power law but is not significantly influenced by molecular weight. Particles with highly elongated cellular pores without lamellar formation show intermediate pore dimensions between the above two limiting morphological types. Analysis of variance and post hoc tests indicate that dextran concentration is the most significant factor in affecting the pore dimensions. The SFD dextran particles herein described could find use in pulmonary drug delivery due to their high porosity and biocompatibility of the matrix material.
Created from Fastlane, Scopus look-up